Performance of graphene oxide-supported Co3O4 with assisted urea as electrocatalysts for oxygen reduction reaction in PEMFCs - Nur Ubaidah Saidin,; Nurul Noramelya Zulkefli,; Nor Ezzati Amira Mustapa Padzir,; Nurazila Mat Zali,; Thye, Foo Choo; Rozan Mohamad Yunus,; Mohd Shahbudin Masdar, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this work, cobalt oxide (Co3O4) nanoparticles supported on a graphene oxide (GO) electrocatalyst were synthesized using a simple and low-cost hydrothermal route for oxygen reduction reaction (ORR) in fuel cells. The effects of varying the urea concentration on the physicochemical and electrochemical characteristics were investigated in alkaline media using field emission scanning electron microscope (FESEM), X-ray diffraction (XRD), Raman spectroscopy, cyclic voltammetry (CV), linear sweep voltammetry (LSV), and chronoamperometry. The electrocatalyst prepared using cobalt acetate tetrahydrate and urea with a molar ratio of 1:1 exhibited the best ORR activity where the highest onset potential (Eonset) at 0.88 V through four-electron mechanism at 25 °C. The synthesized electrocatalyst also showed improved stability compared with Pt/C. Although CN1-1 exhibits a lower power density (37.9 mW cm⁻2) compared to Pt/C (173.6 mW cm⁻2), it is still expected to be suitable as an ORR electrocatalyst for proton exchange membrane fuel cells (PEMFCs).